Pengaruh pH dan Waktu Kontak Terhadap Adsorpsi Logam Zn(II) pada Komposit Arang Eceng Gondok Termodifikasi Kitosan-Epiklorohidrin - Dahlena Ariyani; Noor Cahaya; Dwi Rasy Mujiyanti (Syarif Hidayatullah State Islamic University, 2018)
A study of the effect of pH and time contact on the adsorption of Zn (II) metal on the charcoal of water hyacinth modified chitosan-epichlorohydrin composites has been performed. This study aims to determine the effect of pH and time on Zn (II) adsorption on the charcoal of water hyacinth modified chitosan-epichlorohydrin. Adsorption of Zn (II) metal on the charcoal of water hyacinth modified chitosan-epichlorohydrin composites was tested for pH with variations in pH 2 to 7 and contact time with variations of 15-75 minutes. The results showed that Zn (II) adsorption reached optimum at pH 4 and contact time for 30 minutes was 87.1%.